SELF-DEVELOPMENT AND MATURITY: THE PSYCHOLOGICAL JOURNEY OF THREE BLACK WOMEN CHARACTERS IN A RAISIN IN THE SUN - Ferreira, Kelly Cristina Torres de Barros (Em Tese, 2005)
This study aims at analyzing the psychological journey towardsself-development and maturity of Mama, Ruth and Beneatha,the triangle of black women characters of A Raisin in theSun. I argue here that each of these three female charactersundergoes a process of personal growth in the play.